2020
DOI: 10.1080/14778238.2020.1785348
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic knowledge management strategy development in international non-governmental organisations

Abstract: Knowledge management strategies are important for firms' competitive positioning. This paper examines how knowledge management codification and personalization strategies are developed in response to environmental and organizational dynamics in an international non-governmental organisation. A longitudinal case study of the organisation's strategic reformulation of its KM strategy over a 2.5 period is drawn upon. The research examines how pressures in the firm's operating environment led to the organisation id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…The original article by Hansen et al (1999) proposed a static optimal 80:20 position between codification and personalisation strategies requiring one strategy to be dominant. More recent research has found the strategies complementing each other with neither predominant (Mukherji, 2005) and highly correlated, suggesting a mutually reinforcing relationship (Kumar and Ganesh, 2011; Walsh and Lannon, In Press). Such findings have led researchers to question the 80:20 split, instead arguing that the two strategies have a symbiotic relationship, each receiving benefit from the other, neither being predominant (Venkitachalam and Willmott, 2013; Jaismuddin et al , 2005) and that to take a more dynamics perspective allows both strategies to be enhanced (Scheepers et al , 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The original article by Hansen et al (1999) proposed a static optimal 80:20 position between codification and personalisation strategies requiring one strategy to be dominant. More recent research has found the strategies complementing each other with neither predominant (Mukherji, 2005) and highly correlated, suggesting a mutually reinforcing relationship (Kumar and Ganesh, 2011; Walsh and Lannon, In Press). Such findings have led researchers to question the 80:20 split, instead arguing that the two strategies have a symbiotic relationship, each receiving benefit from the other, neither being predominant (Venkitachalam and Willmott, 2013; Jaismuddin et al , 2005) and that to take a more dynamics perspective allows both strategies to be enhanced (Scheepers et al , 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As discussed in the previous section existing studies have identified that service process codification using ICTs can support either standardisation or customisation (Sundbo, 1994; Monnoyer, 2003; Rust and Miu, 2006; Rust and Huang, 2014) which are being squeezed (Sundbo, 2002) in response to customer needs and cost-efficiency. All three service strategies are supported by ICTs and knowledge management strategies (Hansen et al , 1999) which can dynamically change (Scheepers et al , 2004; Venkitachalam and Willmott, 2013; Walsh and Lannon, In Press). Consequently, as the literature indicated that the underlying service strategy also changes, to achieve a balance between standardisation and customisation through modularity (Nordin et al , 2011; Olivia and Kallenberg, 2003; Sundbo, 2002) design principles from knowledge management strategies can be usefully drawn upon and integrated into service design.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides increased access to the organization's explicit knowledge and allows articulating an organizational response in real time (Belkhodja and Daghfous, 2021; Kianto et al. , 2019; Walsh and Lannon, 2020). Nevertheless, technological turbulence has been generically addressed thus fur, and this explains the lack of studies specifically exploring the effects of turbulence caused by AI.…”
Section: Introductionmentioning
confidence: 99%
“…However, the debate over knowledge management strategies and improvisation remained in the pre-digital era: even recent studies continue to focus on the tacit and explicit knowledge that people generate and use, without acknowledging the changes emerging with the digital era. In general, mainstream research continues to show that knowledge strategies favor improvisation (Belkhodja and Daghfous, 2021; Mamédio et al , 2022; Walsh and Lannon, 2020). However, preliminary evidence argues otherwise, indicating that technological turbulence generated by AI increases knowledge concealment (Arias-Pérez and Vélez-Jaramillo, 2021).…”
Section: Introductionmentioning
confidence: 99%